The Effect of Human Resource Management Practices and Job Satisfaction on Employee Performance: A Proposed Research Framework at Palestinian Municipalities - Omar Jamil Ahmed Muqedi; Khairunneezam Mohd Noor (IJIRSET, 2024)
Non-Indexed Publication